Serial Measurements of Refractive Index, Glucose and Protein to Assess Gastric Liquid Nutrient Transport—A Proof-of-Principal Study - Wittstock, Matthias; Kästner, Matthias; Kolbaske, Stephan; Sellmann, Tina; Porath, Katrin; Patejdl, Robert (Frontiers in Nutrition, 2022)
Abstract Delayed gastric emptying contributes to complications as aspiration or malnutrition. Among patients suffering from acute neurological diseases, motility disorders are prevalent but poorly understood. Thus, methods to measure gastric emptying are required to allow for appropriate adaptions of individual enteral nutrition algorithms. For enterally fed patients repetitive concentration measurements of gastric content have been proposed to assess gastric emptying. This approach can be used to calculate the gastric residual volume and transport of nutrition formula, but it has not yet been implemented in clinical routine. The aim of this study was to investigate whether refractometry or other likewise straightforward analytical approaches produce the best results under in vitro conditions mimicking the gastric milieu. We measured nutrition formula in different known concentrations, either diluted in water or in simulated gastric fluid, with each of the following methods: refractometer, handheld glucose meter and Bradford protein assay. Then, in enterally fed patients suffering from acute neurological disease, we calculated gastric residual volumes and nutrition transport and tested possible associations with clinical parameters. In water dilution experiments, nutrition formula concentrations could be assessed with the readout parameters of all three methods. Refractometry yielded the most precise results over the broadest range of concentrations and was biased least by the presence of simulated gastric fluid (detection range for Fresubin original fibre, given as volume concentration / normalized error of regression slope after incubation with water or simulated gastric fluid: 0 – 100% vs. 0-100% / 0.5% vs. 3.9%; glucose-measurement: 5-100% vs. 25-100% / 7.9 % vs. 6.1%; Bradford-assay: 0% - 100% vs. 0%-100% / 7.8% vs 15.7%). Out of 28 enterally fed patients, we calculated significant slower nutrition transport in patients with higher blood glucose (Rho -0.391; p = 0.039) and in patients who received high-dose sufentanil (Rho -0.514; p = 0.005). Also, the calculated nutrition transport could distinguish patients with and without feeding intolerance (Median 6 ml/h vs. 17 ml/h; Mann-Whitney test: p = 0.002). The results of our study prove that refractometry is a suitable and cost-effective method to assess gastric emptying and to enhance research on gastrointestinal complications of stroke.